Cardiovascular responses induced by selective adenosine A2A and A2B receptor agonists - Wragg, Edward (2023)
Adenosine is an important modulator of the cardiovascular system, acting at four GPCRs, known as the adenosine receptors. A crucial role of two of those receptors, adenosine A2A and A2B receptors, is the induction of vasodilation in resistance arteries that comprise vascular beds across the body, leading to an increase in the ease with which blood flows, known as vascular conductance, in these beds. As a result of these properties, both A2 receptors have been suggested to have therapeutic potential in treating hypertension and other diseases associated with reductions in blood flow to various regions of the body. However, adenosine receptor expression across the different vasculature beds that make up the circulatory system is neither universal nor ubiquitous, and neither are the physiological changes induced by activation of these receptors; different regions of the body have different sensitivities and responses to adenosine through differences in adenosine receptor expression and function across the body. To gain a greater understanding of how A2A and A2B receptors influence the cardiovascular system, this project aimed to investigate the physiological consequences and potential uses of adenosine A2A and A2B receptor activation on the regional flow of blood in the renal, mesenteric and hindquarter vascular circulations, in conscious, freely moving rats, using Doppler flowmetry.